Efektivitas Program Pelayanan Langsung Jadi Administrasi Kependudukan di Desa Tegal Harum, Kecamatan Denpasar Barat - Purdana, I Made; Pandawani , Ni Putu; Sumantra , I Ketut; Sudipa , I Nyoman (Jurnal Ilmiah Administrasi Publik, 2025)
This study aims to analyze the effectiveness of the Direct Administration Service Program (Pelangi Adminduk) in Tegal Harum Village, West Denpasar District. This study uses a quantitative method, with a population of all households in Tegal Harum Village totaling 3,325 households. A simple random sampling technique was used, resulting in 357 households as the sample. Data were analyzed using research instrumentation tests and descriptive/efficiency. The research results indicate that: (1) The Pelangi Adminduk program in Tegal Harum Village is already effective, as demonstrated by organizational factors and high service recipient satisfaction; (2) The constraints affecting the effectiveness of the Pelangi Adminduk program include existing regulations and employee awareness; (3) Solutions to address these constraints involve (a) improving existing regulations to make them easier to understand and apply, and (b) enhancing employee awareness through intensive socialization.